Ação da nitrendipine na aterogênese experimental - Milach, Carlos O; Amaral, Daoiz Mendoza; Mendoza, Raul A.; Juliano, Maria Ines; Gomes, José (VITTALLE - Revista de Ciências da Saúde, 2017)
Ver no documento.